IMPLEMENTASI KEBIJAKAN PENATAAN SISTEM ADMINISTRASI PELAYANAN KEPEGAWAIAN DAERAH - Chalid Sahuri, Amarullah Aman, Febri Yuliani, (Jurnal Ilmu Administrasi Negara, 2019)
Policy Implementation, Regional Staffing Services. This study aims to determine the implementation of the administration system management policy for the regional personnel services of Siak Regency. This study uses a qualitative descriptive research method approach. Primary data is obtained directly through interviews from key informants, namely the Head of the Regional Personnel Agency, Head of Staff Administration, Head of the Sub-Section, Head of the Welfare Sub-Sector and Civil Servants. Secondary data obtained from research documents. The results of the study indicate that there are results achieved from the application of Government Policy No. 31 of 2009 in the field of information and communication technology. This success is also supported by factors that influence the policy, starting from the communication factor supporting the successful implementation of Government Regulation Number 31 of 2009 in the Siak Regency Regional Civil Service Agency, but from the resource factor it is still inadequate in implementing the government regulation policy. Likewise from the implementing attitude factors and bureaucratic structure factors.